Respuesta :

Answer:

The equation becomes

[tex]7x+6 = 10x-12[/tex]

Thus, the number = x = 6

Step-by-step explanation:

Let 'x' the number

seven times a number = 7x

Six more than seven times a number = 7x+6

10 times the number -12 = 10x-12

Given that Six more than seven times a number equals 10 times the number -12.

Thus, the equation becomes

[tex]7x+6 = 10x-12[/tex]

We can further solve for x

[tex]7x+6 = 10x-12[/tex]

[tex]6+12 = 10x-7x[/tex]

[tex]18 = 3x[/tex]

[tex]x = 6[/tex]

Thus, the number = x = 6